Comparison of the Thresholds of Households' Exposure to Catastrophic Health Expenditure in Iran and Brazil, and Selection of the Most Appropriate Threshold - Arash RASHIDIAN; Ali AKBARI SARI; Seyed Mostafa HOSEINI; Moslem SOOFI; Hoseyn AMERI (Tehran University of Medical Sciences, 2018)
Background: Different definitions are nowadays adopted to estimate the threshold of exposure of households to catastrophic health expenditures and different thresholds are used in various studies. This study was conducted to compare these thresholds and select the most appropriate threshold for defining catastrophic health expenditure in Iran and Brazil. Methods: In this cross-sectional study, data were collected from 592 households from District 17 of Tehran, Iran, and 869 households from Porto Alegre, Brazil in 2013. Firstly, catastrophic health expenditures were calculated using two common proportions, i.e. out-of-pocket health payments, as a proportion of total cost and as a proportion of ability to pay. These proportions were analysed using the Receiver Operating Characteristic (ROC) curve and Kappa coefficient. Results: The appropriate cut off point for the thresholds of 5%, 10%, 15%, and 20% of the total expenditure was 0.52, 0.34, 0.28, and 0.46 in Iran, and 0.44, 0.36, 0.28, and 0.23 in Brazil, respectively. The appropriate cut off point for the thresholds of 20%, 25%, 30%, 35%, and 40% of ability to pay was 0.31, 0.28, 0.25, 0.34, and 0.40 in Iran and 0.36, 0.34, 0.30, 0.38, and 0.46 in Brazil, respectively. Conclusion: The appropriate cut off point for the proportion of out-of-pocket health payments to total expenditure and proportion of health expenditure to ability to pay was the threshold of 20% of total expenditure and 35% of ability to pay, respectively.